2016
DOI: 10.1074/jbc.m115.712976
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Cancer Stem Cell Marker CD133 and Src Protein Promotes Focal Adhesion Kinase (FAK) Phosphorylation and Cell Migration

Abstract: CD133, a widely known cancer stem cell marker, has been proved to promote tumor metastasis. However, the mechanism by which CD133 regulates metastasis remains largely unknown. Here, we report that CD133 knockdown inhibits cancer cell migration, and CD133 overexpression promotes cell migration. CD133 expression is beneficial to activate the Src-focal adhesion kinase (FAK) signaling pathway. Further studies show that CD133 could interact with Src, and the region between amino acids 845 and 857 in the CD133 C-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 57 publications
0
46
0
Order By: Relevance
“…Their regulation by certain subunits of Arp2/3 complex, notably p34‐Arc/ARPC2 and vinculin, has been proposed . Similarly, Liu et al have demonstrated that the interaction of prominin‐1 with Src protein promotes the phosphorylation of focal adhesion kinase and cancer cell migration …”
Section: Discussionmentioning
confidence: 92%
“…Their regulation by certain subunits of Arp2/3 complex, notably p34‐Arc/ARPC2 and vinculin, has been proposed . Similarly, Liu et al have demonstrated that the interaction of prominin‐1 with Src protein promotes the phosphorylation of focal adhesion kinase and cancer cell migration …”
Section: Discussionmentioning
confidence: 92%
“…It suggested a role of CD133 in the initiation of colon cancer metastasis. Knockdown of CD133 in SW620 human colon cancer cells impaired cell migration through reduced phosphorylations of Src-focal adhesion kinase (FAK) and this is due to a failure of forming a complex of CD133, Src, and FAK (Liu et al, 2016). Furthermore, the interaction between CD133 and Src is required for CD133-induced cell motility by activation of Src downstream target FAK.…”
Section: Cd133 and Its Signaling In Cancer Metastasismentioning
confidence: 99%
“…The interaction between phosphorylated CD133 (Y828 residue) and the PI3K regulatory subunit p85 activates PI3K/Akt pathway to promote tumorigenesis in glioma stem cells [8]. In addition, interaction between the C-terminal domain of CD133 and Src enhances the phosphorylation of FAK and promotes tumor cell migration [9]. These observations imply the critical role of CD133 in tumor initiation and metastasis.…”
mentioning
confidence: 96%
“…Existing evidence suggests that interaction of CD133 and VEGF promotes tumor growth by supporting angiogenesis [7]. In addition, interaction between the C-terminal domain of CD133 and Src enhances the phosphorylation of FAK and promotes tumor cell migration [9]. In addition, interaction between the C-terminal domain of CD133 and Src enhances the phosphorylation of FAK and promotes tumor cell migration [9].…”
mentioning
confidence: 99%